Physical Methods for Stimulation of Plant and Mushroom Development - El-Esawi, Mohamed (IntechOpen, 2018)
Chemical additives used for increasing plant productivity can contaminate the raw materials used in food production. Physical methods represent alternative promising sources for stimulating plant and mushroom development and increasing vegetable production. Many physical factors are currently used for plant treatment, including electromagnetic waves, optical emission, laser, magnetic field, gamma rays and ultrasound and ionizing radiation. This book discusses these physical methods for stimulation of plant and mushroom development and seed invigoration. Current research trends, future research directions and challenges are also discussed. This book will be of interest to many readers, researchers and scientists who can find this information useful for the advancement of their research works towards a better understanding of physical methods in plant and mushroom development.